Facial discoid dermatosis: A cosmetically disfiguring and challenging condition to treat - S. Rahmatulla; K. Batta; F. Tatnall; D. Sandhu; V. Brown (Wiley, 2021)
Abstract Facial discoid dermatosis (FDD) is a recently described condition comprising discrete facial papulo‐squamous lesions. We report three cases that clinically and histologically resemble FDD and demonstrate its resistance to treatment. Awareness of this new clinical entity will allow early diagnosis and the ability to make patients aware that there is unlikely to be a successful treatment. However, our study suggests that although FDD can persist for many years, it appears to remain stable.